Likely clinical depression and HIV-related decline in antiretroviral therapy untreated women who seroconverted during participation in microbicide trials in sub-Saharan Africa. (June 2021) - Rael, Christine T; Roberts, Sarah; Ibitoye, Mbolaji; Gorbach, Pamina M; Palanee-Phillips, Thesla; Harkoo, Ishana; Mbilizi, Yamikani; Panchia, Ravindre; Siva, Samantha; Tembo, Tchangani; Agwau Akello, Carolyne; Balkus, Jennifer; et al.
Depression worsens HIV outcomes in populations treated with antiretroviral therapy (ART) medications. Data are limited on the relationship between depression and HIV in untreated populations in sub-Saharan Africa. We aimed to identify associations between likely clinical depression, alcohol use, social support by partners, and HIV viral load (VL) among ART untreated women who recently became HIV positive and enrolled in the Microbicide Trials Network (MTN)-015 study. Analyses used cross-sectional data collected at baseline in MTN-015. Participants in this analysis ( N = 190) enrolled from other MTN trials were not receiving ART and provided data on their HIV disclosure status to their husband or male partner and alcohol use behavior. The dependent variable, VL, was categorized as: low (≤400 RNA copies/mL; 9.1% of participants), medium (401–20, 000 RNA copies/mL; 48.8%), and high (>20, 000 RNA copies/mL; 42.0%). Depression was assessed using eight items from Hopkins Symptom Checklist; a cutoff of ≥1.75 indicated likely clinical depression. Independent variables with a significance of p ≤ 0.05 in unadjusted regressions were included in a regression adjusted for age, education, and time since seroconversion. Depressive symptoms were positively associated with high VL, in the adjusted regression (OR = 1.80; 95% CI = 1.07–3.01). Results suggest that likely having clinical depression may have a biological relationship with HIV disease progression.